Effectiveness of Community Based Interactive Approach Method on Community Perception in Utilizing Gotu Kola - Rahmawati, Fitria; Suhita, Byba Melda; Widyowati, Agustin (GoAcademica Research & Publishing, 2025)
Gotu kola is a medicinal plant that is readily accessible, yet it remains underutilized. This research aims to analyze the effectiveness of the Community Based Interactive Approach method on community perception in utilizing gotu kola in Mojorejo Village, Batu City. The research design used a quasi-experimental control group pretest-posttest design. The sampling technique was purposive, with 20 respondents in the treatment group and 20 in the control group. Perception before and after the intervention was measured using a questionnaire. Validity and reliability tests were conducted on the research instruments before use. The research results show that before implementing the method, 80% of respondents' perceptions were categorized as high. After implementing the Community Based Interactive Approach method, all respondents' perceptions increased to the high category. Statistical results using the Wilcoxon test showed an effect of Community Based Interactive Approach on perception in the treatment group (p < 0.001). The Community Based Interactive Approach method effectively improves the community's perceptions in utilizing gotu kola.